2020
DOI: 10.12659/msm.918537
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation of Elderly Patients with Severe Burns at a Major Burn Center in Southwest China

Abstract: Background: The treatment of elderly patients with severe burns is difficult and the mortality rate is high. The aim of this study was to investigate the epidemiological features of elderly patients with severe burns. Material/Methods: Data from 109 elderly patients with severe burns between January 2009 and December 2018 were retrospectively analyzed. Demographic data, clinical characteristics, treatments, and outcomes were statistically analyzed. Results: Among the 109 elderly patients with severe burns, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
7
10
2
1
Order By: Relevance
“…In our study, the dominant burn agent was ames _inconsistent with some studies (4,20,21) and similar to some others (12,22)_ but in survivors, the most common agent was scald that results from the slight dominancy of women, indoor accidents, and age-related medical conditions of the elderly like reduced reaction time, visual impairments, and a limited range of motions. Similar to previous studies (23)(24)(25), inhalation injury was a risk factor for poor prognosis in the elderly.…”
Section: Resultssupporting
confidence: 56%
“…In our study, the dominant burn agent was ames _inconsistent with some studies (4,20,21) and similar to some others (12,22)_ but in survivors, the most common agent was scald that results from the slight dominancy of women, indoor accidents, and age-related medical conditions of the elderly like reduced reaction time, visual impairments, and a limited range of motions. Similar to previous studies (23)(24)(25), inhalation injury was a risk factor for poor prognosis in the elderly.…”
Section: Resultssupporting
confidence: 56%
“…The finding of this study reveals that males are predominantly affected as compared to females but this does not reach the significant statistical difference this finding does not agree with the findings of other researchers [21][22][23][24][25][26][27][28] while other study reported a similar finding in gender composition ratio [29] but our finding disagrees with the findings of other researchers who found that females were suffered burn injuries significantly more than males [30][31][32] . Regarding age of patients,this study clarifies that the vast majority of the victims are below 30 years of age and mainly children below ten years, this result is similar to result reported by other studies [26,33] and this explain why that most of the burn victims were male in gender due to that the boys are more susceptible to burn accidents because they are more active than the girls.…”
Section: Discussioncontrasting
confidence: 99%
“…This study further confirmed the superiority and reliability of PCCO monitoring compared with traditional monitoring. Nowadays, the mortality of severe burns patients worldwide is still at a relatively high level, and has been reported as ranging between 12.2% and 47.6% (3,21,22). As our burns center has many years of experience in severe burns diagnosis and treatment, the mortality is maintained at a relatively low level, and in this study, the overall mortality of enrolled patients was 3.7% in the control group and 4.9% in the study group, respectively.…”
Section: Discussionmentioning
confidence: 51%